Karakteristik Jamur Sagu (Volvariella sp.) Endemik Papua - Abbas, Barahima; Listyorini, Florentina Heningtyas; Martanto, Eko Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Sago mushrooms (Volvariella sp.) were known as edible mushroom which grow sporadically on decay of sagopith waste in Papua. Local people in Papua always hunting and harvesting sago mushrooms which are growingwild on decayed sago pith waste. People were enjoyed consumption of sago mushrooms. The aims of this researchwere to study nutrient contents of sago mushrooms as well as to distinguish the difference of morphologicalcharacters between sago mushroom and paddy straw mushroom which popular in Indonesia. Sago mushroomswere collected from Yapen regency, Papua Province and measured for their nutrient contents and morphologicalcharacteristics. The results of this research showed that morphological characteristic of sago mushroom differfrom paddy straw mushroom and other edible mushroom. Nutrient contents of Sago mushroom per 100 gramsfresh weigh were follows: protein 4.00 g, carbohydrate 2.99 g, lipid 0.19 g, calcium 11.53 mg, phosphorous 0.31 g,and potassium 165.05 mg. Nutrient contents of sago mushroom were very different from that of paddy strawmushroom and others mushrooms of the genus Volvariella. Based on morphological characteristic and nutrientcontents of Sago mushrooms, we suggest that sago mushrooms is a new species.